2023
DOI: 10.48162/rev.39.097
|View full text |Cite
|
Sign up to set email alerts
|

Does harmonization reduce the impact of SPS measures on agricultural exports? An assessment from the Chilean fruit sector

Abstract: Non-tariff measures (NTMs) are relevant to agricultural trade policies, especially since trade negotiations have significantly decreased tariffs. Countries impose Sanitary and Phytosanitary Measures (SPS), a technical NTM, to protect human, animal, and plant health by regulating specific food quality and safety aspects. This article aims to assess the impact of SPS measures imposed by Chile’s main trading partners on agricultural trade, specifically on the value of fruit exports. It also seeks to determine the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Geetha et al (2020) argue that there is a necessity for the establishment of standardized safety and quality regulations in worldwide surveillance systems, as well as the adoption of science-based requirements and procedures, among prominent importing nations. According to the findings of Boza et al (2023), the implementation of harmonization measures has been shown to mitigate the adverse impacts of foreign sanitary and phytosanitary (SPS) regulations on export activities.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Geetha et al (2020) argue that there is a necessity for the establishment of standardized safety and quality regulations in worldwide surveillance systems, as well as the adoption of science-based requirements and procedures, among prominent importing nations. According to the findings of Boza et al (2023), the implementation of harmonization measures has been shown to mitigate the adverse impacts of foreign sanitary and phytosanitary (SPS) regulations on export activities.…”
Section: Literature Reviewmentioning
confidence: 99%